Rainforest refugia and Australia's Wet Tropics - Schneider, C. (1999)
Comparison of mitochondrial DNA variation among populations of three endemic lizard species in Australia's Wet Tropics rainforest reveals clear evidence of population-level response to Pleistocene rainforest contraction and subsequent expansion. This pattern is repeated in two separate rainforest regions (natural replicates), between which populations have been separated for several million years. Despite evidence for isolation in rainforest refugia, historically reduced effective population size, and recent range expansion, little or no detectable phenotypic evolution has occurred among populations, even those isolated for several million years. These observations suggest that long-term isolation per se, even when combined with major reductions in population size and opportunities for drift and founder effects, is unlikely to be the primary process driving phenotypic divergence and speciation of rainforest vertebrates.